The Design Of Social Return On Investment Calculation Standard Operation Procedure For PT ASDP Indonesia - Fathin, Muhammad; Anggoro, Yudo (Politeknik Negeri Bandung, 2025)
Developing a Standard Operating Procedure (SOP) and incorporating Social Return on Investment (SROI) into the CSR tree planting program are the main objectives of this study. SROI provides a framework for evaluating the approach's economic, social, and environmental worth by connecting activities with goals for financial gains and carbon offsets. The SOP offers detailed instructions for choosing species, planting methods, and maintenance, with a focus on compact planting spaces for effectiveness and impact. a Comprehensive Monitoring, Reporting, and Verification (MRV) systems combined with stakeholder collaboration are intended to promote sustainability, transparency, and ongoing development. These tactics guarantee that social, economic, and environmental objectives are met in a harmonious way.